RELATIONSHIP OF EARTH TIDES TO ACOUSTIC EMISSIONS IN THE INTERIOR OF THE EARTH - Belyakov A.S.; Vereshchagins G.M.; Kuznetsov V.V. (My University, 1990)
It is not illogical that acoustic noise in the interior of the earth should be correlated with the moon- and sun-induced earth tides; but while some published data support this view, other investigators cast doubt on the reliability of the results and conclusions. We have recorded acoustic noise for a sufficiently long period to allow reliable identification of such a correlation. The recording was done in drillhole No. 123 of the Rechit oil field in the Gomel region of Belorussia. The diurnal peak in the intensity of burst noise occurs in early morning and coincides with the time of greatest rate of crust-stretching deformation produced by earth tides. This result confirms that the emission properties of the geophysical medium are correlated with its stress and strain state, induced by earth tides. These conclusions corroborate the main principles of Sadovskiy's model of the geophysical medium, which assumes a medium that undergoes constant alteration and emits noise over a wide range of frequencies related to the characteristic block structure of the crust.